1983
DOI: 10.2177/jsci.6.249
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up studies of immunological disorders in patients with ataxia-telangiectasia

Abstract: We studied a 10 years old boy with ataxia-telangiectasia suffered from T cell ALL.We characterized his tumor cell with immunological techniques.His affected female sib, who had very low serum IgG, IgA and elevated IgM concentration, died from pulmonary infection at 10 years old. In his family members, there were high frequency of cancers.The patient showed moderate cellular immune deficiency such as deficient delayed type skin hypersensitivity and low lymphocyte counts during early childhood, but did not show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Although the mechanisms by which AEDs cause HGG are unclear, low immunoglobulin subclass concentrations in children treated with carbamazepine or sodium valproate have been attributed to the effect of AEDs on B cell maturation or regulatory T lymphocytes, which directly affect immunoglobulin isotype production [34, 40]. Dosch et al [14] observed that AEDs impacting immunoglobulin concentrations block sodium channels; therefore, it may be possible that this mode of action causes the observed side effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which AEDs cause HGG are unclear, low immunoglobulin subclass concentrations in children treated with carbamazepine or sodium valproate have been attributed to the effect of AEDs on B cell maturation or regulatory T lymphocytes, which directly affect immunoglobulin isotype production [34, 40]. Dosch et al [14] observed that AEDs impacting immunoglobulin concentrations block sodium channels; therefore, it may be possible that this mode of action causes the observed side effect.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights that four weeks of conservative treatment could be tried before circumcision reducing the risk of anesthesia 16 as well as complications associated with surgery. 16,17 A tight foreskin may manifest with symptoms such as itching, smegma deposits, straining, ballooning, balanoposthitis, dysuria, or urinary infection termed as symptomatic or pathological phimosis.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Gentle retraction of the prepuce, known as physiotherapy, was suggested as an important factor in the spontaneous resolution of physiologic phimosis. 17 Although forcible retraction of the prepuce should be avoided because of pain, bleeding, adhesion, and cicatrix formation, which might lead to secondary phimosis, careful and gentle retraction has been encouraged for the more rapid resolution of severe physiologic phimosis. 6,17 A previous study found that gentle retraction of the foreskin with topical application, reported a 50% success rate even with placebo cream and physiotherapy and suggested that physiotherapy per se would be effective to resolve physiologic phimosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation